4-Hexylresorcinol-in duced angiogenesis potential in human endothelial cells - Min-Keun Kim; Seong-Gon Kim; Suk Keun Lee (SpringerOpen, 2020)
Abstract Background 4-Hexylresorcinol (4HR) is able to increase angiogenesis. However, its molecular mechanism in the human endothelial cells has not been clarified. Methods As endothelial cells are important in angiogenesis, we treated the human umbilical vein endothelial cells (HUVECs) with 4HR and investigated protein expressional changes by immunoprecipitation high-performance liquid chromatography (IP-HPLC) using 96 antisera. Results Here, we found that 4HR upregulated transforming growth factor-β (TGF-β)/SMAD/vascular endothelial growth factor (VEGF) signaling, RAF-B/ERK and p38 signaling, and M2 macrophage polarization pathways. 4HR also increased expression of caspases and subsequent cellular apoptosis. Mechanistically, 4HR increased TGF-β1 production and subsequent activation of SMADs/VEGFs, RAF-B/ERK and p38 signaling, and M2 macrophage polarization. Conclusion Collectively, 4HR activates TGF-β/SMAD/VEGF signaling in endothelial cells and induced vascular regeneration and remodeling for wound healing.